Safety and activity of RRx-001 in patients with advanced cancer: a first-in-human, open-label, dose-escalation phase 1 study. Issue 9 (September 2015) - Reid, Tony; Oronsky, Bryan; Scicinski, Jan; Scribner, Curt L; Knox, Susan J; Ning, Shoucheng; Peehl, Donna M; Korn, Ron; Stirn, Meaghan; Carter, Corey A; Oronsky, Arnold; Taylor, Michael J; et al.
Summary: Background: Epigenetic alterations have been strongly associated with tumour formation and resistance to chemotherapeutic drugs, and epigenetic modifications are an attractive target in cancer research. RRx-001 is activated by hypoxia and induces the generation of reactive oxygen and nitrogen species that can epigenetically modulate DNA methylation, histone deacetylation, and lysine demethylation. The aim of this phase 1 study was to assess the safety, tolerability, and pharmacokinetics of RRx-001. Methods: In this open-label, dose-escalation, phase 1 study, we recruited adult patients (aged >18 years) with histologically or cytologically confirmed diagnosis of advanced, malignant, incurable solid tumours from University of California at San Diego, CA, USA, and Sarah Cannon Research Institute, Nashville, TN, USA. Key eligibility criteria included evaluable disease, Eastern Cooperative Group performance status of 2 or less, an estimated life expectancy of at least 12 weeks, adequate laboratory parameters, discontinuation of all previous antineoplastic therapies at least 6 weeks before intervention, and no residual side-effects from previous therapies. Patients were assigned to receive intravenous infusions of RRx-001 at increasing doses (10 mg/m 2, 16·7 mg/m 2, 24·6 mg/m 2, 33 mg/m 2, 55 mg/m 2, and 83 mg/m 2 ) either once or twice-weekly for at least 4 weeks, with at least three patients per dose cohort and allowing a 2-week observation period before dose escalation. Samples for safety and pharmacokinetics analysis, including standard chemistry and haematological panels, were taken on each treatment day. The primary objective was to assess safety, tolerability, and dose-limiting toxic effects of RRx-001, to determine single-dose pharmacokinetics, and to identify a recommended dose for phase 2 trials. All analyses were done per protocol. Accrual is complete and follow-up is still on-going. This trial is registered withClinicalTrials.gov, numberNCT01359982 . Findings: Between Oct 10, 2011, and March 18, 2013, we enrolled 25 patients and treated six patients in the 10 mg/m 2 cohort, three patients in the 16·7 mg/m 2 cohort, three patients in the 24·6 mg/m 2 cohort, four patients in the 33 mg/m 2 cohort, three patients in the 55 mg/m 2, and six patients in the 83 mg/m 2 cohort. Pain at the injection site, mostly grade 1 and grade 2, was the most common adverse event related to treatment, experienced by 21 (84%) patients. Other common drug-related adverse events included arm swelling or oedema (eight [32%] patients), and vein hardening (seven [28%] patients). No dose-limiting toxicities were observed. Time constraints related to management of infusion pain from RRx-001 resulted in a maximally feasible dose of 83 mg/m 2 . Of the 21 evaluable patients, one (5%) patient had a partial response, 14 (67%) patients had stable disease, and six (29%) patients had progressive disease; all responses were across a variety of tumour types. Four patients who had received RRx-001 were subsequently rechallenged with a treatment that they had become refractory to; all four responded to the rechallenge. Interpretation: RRx-001 is a well-tolerated novel compound without clinically significant toxic effects at the tested doses. Preliminary evidence of activity is promising and, on the basis of all findings, a dose of 16·7 mg/m 2 was recommended as the targeted dose for phase 2 trials. Funding: EpicentRx (formerly RadioRx).